INOVASI BIROKRASI PELAYANAN PUBLIK BIDANG SOSIAL TENAGA KERJA DAN TRANSMIGRASI DI KABUPATEN KUDUS - Aufarul Marom (Departemen Administrasi Publik, Universitas Diponegoro, 2015)
One thing that can be felt directly by the people of the presence ofgovernment and bureaucracy is a public service. Through this public service tothe community will be able to assess the how big is the quality of service that hasbeen provided by the institutions of public services to the community as well asto the level where people feel satisfied with the existing services. Publiccomplaints against the lack of quality of service is one indicator that shows theinadequacy of the services provided by the bureaucratic apparatus. Demands andneeds of the community is a challenge for bureaucracy to be able to provide thebest service and to be able to perform its function properly. To that end,bureaucratic institutions need to implement a service improvement strategy thatresponds to the needs of people who wish to improve the quality of service.Based on the results of the study showed that the social field of manpower andtransmigration in Kudus Regency has two very popular service innovation andseeded. The first innovation is innovation that is the home of surgical services forKudus residents and citizens of the disadvantaged have the opportunity toreceive services such as house surgeon with the requirements that have beenset. The second innovation in the form of a death benefit up to one million rupiahfor the Kudus citizens who are entitled to obtain it. The conclusion of the researchshowed that the Public Service Innovation in Dinsosnakertrans Kudus Regencyhas been done with a Yellow Card service opportunities through on-line. SocialAssistance Home Surgery is often still experiencing problems because ofincomplete to the terms and conditions required for the maintenance of suchassistance. Social Assistance Benefit Death still constrained quite a long time toreduce the assistance because disbursement procedure that is long enough.Key words : Innovation; Bureaucracy; Service; Dinsosnakertrans